The coherent combination of fibre lasers - Towards realistic applications - Tudor, P; Corner, L; Walczak, R (AIP Publishing, 2017)
To drive a laser-plasma wakefield, high peak-power laser pulses are required. For useful accelerator applications, it is also necessary to have driving lasers with high efficiency, repetition rates, and average power. The coherent combination of Ytterbium-doped fibre laser amplifiers is a promising potential solution, and previous work has demonstrated the successful combination of near-identical ultrafast fibre lasers. We report here the combination of significantly mismatched Ytterbium-doped photonic crystal fibre amplifiers with a combined efficiency of 96%, while the locked power output remained stable for 6 hours. The combined output of the system had a total gain of 12 dB, with no detrimental effect on the compressed pulse width observed.